2008
DOI: 10.1055/s-2008-1038191
|View full text |Cite
|
Sign up to set email alerts
|

Halluzinogen-induzierte psychische Störungen

Abstract: Acute psychotic syndromes in adolescents are rarely due to intoxications with hallucinogenic drugs. However, clinical relevance of flashback phenomena as post-hallucinogenic psychiatric disorder has to be disputed. Because of the high popularity of biogenic hallucinogens and LSD knowledge of intoxications and resulting psychiatric disorders as well as medical complications and therapeutical approaches are clinically important. Especially intoxications with drugs of herbal origin like tropanalcaloids play an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…The actual incidence of HPPD is not known and depends on the prevalence of use in different countries, but epidemiologic information is scarce. Hermle et al (2008) reviewed MEDLINE data for 1997-2007, searching for reports of hallucinogen-induced psychosis, flashbacks, and HPPD. The authors reported that adolescent intoxication with psychedelic drugs rarely produced acute psychotic syndromes, further stating that "The clinical relevance of flashback phenomena as a posthallucinogenic psychiatric disorder has to be disputed.…”
Section: Hallucinogen Persisting Perception Disordermentioning
confidence: 99%
“…The actual incidence of HPPD is not known and depends on the prevalence of use in different countries, but epidemiologic information is scarce. Hermle et al (2008) reviewed MEDLINE data for 1997-2007, searching for reports of hallucinogen-induced psychosis, flashbacks, and HPPD. The authors reported that adolescent intoxication with psychedelic drugs rarely produced acute psychotic syndromes, further stating that "The clinical relevance of flashback phenomena as a posthallucinogenic psychiatric disorder has to be disputed.…”
Section: Hallucinogen Persisting Perception Disordermentioning
confidence: 99%
“…Our patient, now 36 years old and currently in an apprenticeship in a tree nursery, had been experiencing persistent visual disturbances from the age of 18 onwards following a year long recreational use of LSD, cannabis, alcohol and cocaine. These disturbances manifested themselves variously as photopsia (included small intensely coloured, flickering, geometric shapes within the entire visual field), afterimages personality disorder, mental trauma in childhood/adolescence) may constitute such variables [7,8]. In this context it is noteworthy that a whole range of non-hallucinogenic psychotropic drugs are also known to elicit complex visual perception disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological approaches to HPPD are currently based on a few uncontrolled single case observations with sometimes contradictory recommendations as to the clinical usefulness of clonidine, SSRIs, benzodiazepines, risperidone, olanzapine and naltrexone (Table 2). Thus, no sound clinical guidelines exist for a rational pharmacological treatment of HPPD [3,7,37,38]. Moreover, it remains unclear whether the "successful" treatments listed in Table 2 are the result of actual therapeutic efficacy or spontaneous remissions.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of both symptom types is unknown but thought to be low [41; 42]. However, there is a history of claiming that psychedelic-use can be directly causal of their emergence [42]. Here, we define 'psychedelics' as "LSD, psilocybin/magic mushrooms/truffles, DMT, ayahuasca, 5-MeO-DMT, mescaline (synthetic or plant derived), or the psychedelic-like drug MDMA/ecstasy".…”
Section: Introductionmentioning
confidence: 99%